The fate of the day : the war for America, Fort Ticonderoga to Charleston, 1777-1780 - Atkinson, Rick (Atkinson, Rick. Revolution trilogy, 2025)
"The first twenty-one months of the American Revolution--which began at Lexington and ended at Princeton--was the story of a ragged group of militiamen and soldiers fighting to forge a new nation. By the winter of 1777, the exhausted Continental Army could claim only that it had barely escaped annihilation by the world's most formidable fighting force. Two years into the war, George III is as determined as ever to bring his rebellious colonies to heel. But the king's task is now far more complicated: fighting a determined enemy on the other side of the Atlantic has become ruinously expensive, and spies tell him that the French and Spanish are threatening to join forces with the Americans. Prize-winning historian Rick Atkinson provides a riveting narrative covering the middle years of the Revolution. Stationed in Paris, Benjamin Franklin woos the French; in Pennsylvania, George Washington pleads with Congress to deliver the money, men, and materiel he needs to continue the fight. In New York, General William Howe, the commander of the greatest army the British have ever sent overseas, plans a new campaign against the Americans--even as he is no longer certain that he can win this searing, bloody war. The months and years that follow bring epic battles at Brandywine, Saratoga, Monmouth, and Charleston, a winter of misery at Valley Forge, and yet more appeals for sacrifice by every American committed to the struggle for freedom."--